Determination of Provenance and Tectonic Settings of Niger Delta Clastic Facies Using Well-Y, Onshore Delta State, Nigeria. (25th December 2014) - Oni, S. O.; Olatunji, A. S.; Ehinola, O. A.
Abstract : Provenance analysis serves to reconstruct the predepositional history of a sediment/sedimentary rock. This paper focuses on the reconstruction of the provenance and tectonic settings of the Niger delta clastic facies using geochemical approach. The main types of geochemical tests include major, trace, and rare earth element (REE) tests. Twenty-one samples of shales and sandstones units were purposely collected from a depth between 1160 and 11, 480 m, grinded, pulverized, and sieved with a <75  μ m. About 5 g was packed and sent to Acme analytical Laboratory Ltd., Vancouver, Canada. The analyses were carried out by both induced coupled plasma-mass spectrometry (ICP-MS) and induced coupled plasma-emission spectrometry (ICP-ES). Bulk-rock geochemistry of major oxides, trace elements, and rare earth elements was utilized for the provenance and tectonic setting determination. Based on the discrimination diagram for major oxides, the probable provenance of the south eastern Delta clastic sediments was mainly of the active continental margins. The bivariate plots of La versus Th, La/Y versus Sc/Cr, and Ti/Zr versus La/Sc and the trivariate plots of La-Th-Sc, Th-Sc-Zr/10, and Th-Co-Zr/10 are all plotted on the fields of active continental margin sediments which is consistent with the known actively opening of a failed arm of triple junction. The trace elements and REE analysis indicates that they are virtually Fe-rich, lithic/quartz arkosic sandstones. The normalizing factors used for the REE are Wakita chondrite. Their rare earth elements (REE) pattern displays high light REE/heavy REE (LREE/HREE) ratio, flat HREE, and a significant negative Eu anomaly which correlate well with the UCC and PAAS average composition. The source area may have contained felsic igneous rocks.